Hubungan antara Kedekatan Hubungan Antarsaudara Kandung dengan Kecenderungan Memaafkan - Fenny; Christiany Suwartono (Fakultas Psikologi Universitas Pancasila, 2010)
The objective of the study was to examine the correlation between siblings relationship with forgiving aspect. Sibling interactions are not without conflict. One simple way to settle the conflict is to forgive. Forgiving will open the way to restore and develop siblings relationship and to erase resentment. Siblings are supposed to have close relationship and therefore are easier for them to forgive each other. However, in real life not all siblings conflicts are ended with forgiving acts. Inability to conduct forgiving acts and to remove hard feelings may influence well being and siblings relationship and will likely raise the same conflict in the future. The result showed significant correlation between sensitivity and warmth. Additional findings demonstrated that there were significant differences between siblings rivalry and age discrepancy, betweensiblings of the same gender and the opposite gender on the aspects of willingness to forgive which was influenced by individual situation or conditions and social environment, and about the obstacles which influenced willingness to forgive. The feelings of getting special treatment, support and close relationship with the parent also yielded significant differences between siblings of the same gender and the opposite gender.